Democratic enlightenment : philosophy, revolution, and human rights 1750-1790 - Israel, Jonathan, 1946- (Oxford University Press, 2011)
The Enlightenment shaped modernity. Western values of representative democracy and basic human rights, gender and racial equality, individual liberty, and freedom of expression and the press, form an interlocking system that derives directly from the Enlightenment's philosophical revolution. This fact is uncontested - yet remarkably few historians or philosophers have attempted to trace the process of ideas from the political and social turmoil of the late eighteenth century to thepresent day. This is precisely what Jonathan Israel now does. He demonstrates that the Enlightenment was an essent.